2018
DOI: 10.3390/cells7110213
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Signatures of Clostridium difficile Stressed with Metronidazole, Vancomycin, or Fidaxomicin

Abstract: The anaerobic pathogen Clostridium difficile is of growing significance for the health care system due to its increasing incidence and mortality. As C. difficile infection is both supported and treated by antibiotics, a deeper knowledge on how antimicrobial agents affect the physiology of this important pathogen may help to understand and prevent the development and spreading of antibiotic resistant strains. As the proteomic response of a cell to stress aims at counteracting the harmful effects of this stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
11
1
Order By: Relevance
“…GntR family members fulfil various biological functions in diverse bacterial groups. Amongst others, GntR-like proteins are involved in resistance to antimicrobial compounds including vancomycin and isoniazid, which inhibit cell wall synthesis [ 59 , 60 , 61 ]. In this study, we found the GntR-like protein CDIF630erm_01007 with significantly altered amounts after the addition of nisin to C. difficile .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GntR family members fulfil various biological functions in diverse bacterial groups. Amongst others, GntR-like proteins are involved in resistance to antimicrobial compounds including vancomycin and isoniazid, which inhibit cell wall synthesis [ 59 , 60 , 61 ]. In this study, we found the GntR-like protein CDIF630erm_01007 with significantly altered amounts after the addition of nisin to C. difficile .…”
Section: Resultsmentioning
confidence: 99%
“…Such divergent results could be potentially explained by differences in either, the applied antimicrobial concentration and the duration of treatment. Indeed, the existing literature points at different effects that can be observed when the same stressor is applied either in shock experiments (exponentially growing cells are treated with sub-lethal concentrations of the stressor) or in long-term stress experiment, where the bacterium is inoculated into a medium already containing the stressor and growth occurs in presence of this stressor for at least 16 h [ 53 , 61 , 65 , 66 ]. Moreover, the applicable concentration of a stressor seems to depend on the experimental setup followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes have been previously shown in a study on proteomic signatures of C . difficile stressed with sub lethal concentrations of MTZ, vancomycin, or fidaxomicin in exponential growth phase [ 56 ]. In addition to their roles in translation, some aminoacyl-tRNAs are also used in pathways directly implicated in antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, fidaxomicin is currently widely used in the treatment of Clostridium difficile infection, especially for recurrent cases. Fidaxomicin was approved in Germany and the US in 2011 for use in the treatment of Clostridium difficile infections in adult patients [17].…”
Section: Introductionmentioning
confidence: 99%